Cameroonian Medicinal Plants: Pharmacology and Derived Natural Products - Efferth, Thomas; Kuete, Victor (Frontiers in Pharmacology, 2010)
Many developing countries including Cameroon have mortality patterns that reflect high levels of infectious diseases and the risk of death during pregnancy and childbirth, in addition to cancers, cardiovascular diseases and chronic respiratory diseases that account for most deaths in the developed world. Several medicinal plants are used traditionally for their treatment. In this review, plants used in Cameroonian traditional medicine with evidence for the activities of their crude extracts and/or derived products have been discussed. A considerable number of plant extracts and isolated compounds possess significant antimicrobial, antiparasitic including anti-malarial, anti-proliferative, anti-inflammatory, anti-diabetes, and antioxidant effects. Most of the biologically active compounds belong to terpenoids, phenolics and alkaloids. Terpenoids from Cameroonian plants showed best activities as anti-parasitic, but rather poor antimicrobial effects. The best antimicrobial, anti-proliferative and antioxidant compounds were phenolics. In conclusion, many medicinal plants traditionally used in Cameroon to treat various ailments displayed good activities in vitro. This explains the endeavor of Cameroonian research institutes in drug discovery from indigenous medicinal plants. However, much work is still to be done to standardize methodologies and to study the mechanisms of action of isolated natural products.